Comparative evaluation of naturally ventilated screenhouse and evaporative cooled greenhouse based on optimal vapor pressure deficit - Shamshiri, R.; Ahmad, D.; Wan Ismail, W.I.; Man, H.C.; Zakaria, A.; Van Beveren, P.; Yamin, M. (2016)
The objective of this study was to compare two closed-field plant production environments for tomato cultivation based on optimal vapor pressure deficit (VPD). Experiment was carried out in tropical lowlands of Malaysia by collecting 11 days of sample data during March (2014), from an evaporative cooled Polycarbonate Panel (PP) covered greenhouse and a naturally ventilated Screenhouse (SH). A computer application was designed and used for VPD calculation and data processing with respect to three light conditions (night, sun and cloud). The average and maximum VPD were respectively equal to 0.97 and 3.81 kPa for SH and 1.19 and 5.1 kPa for PP. The largest differences in the VPD of the two environments were between 2.9 and 3.1 kPa and were observed between hours of 12:30 and 17:30 at sun conditions. Results did not show significant differences in the two environments between hours of 00:00 and 8:00, when inside air temperature was between 24 to 26°C, and relative humidity was near 90%. The hypothesis that the PP, compared to SH, provides VPD closer to the optimal range was rejected. Further analysis of the results showed that linear correlations with R2>0.9 exist between daily averaged VPD of each greenhouses. It was concluded that VPD in the SH was closer to the optimal range in the entire days of experiment. The outcome of this study contributes to knowledge-based information for greenhouse growers by addressing questions about trends in VPD data, peak-hours and light conditions associated with maximum and minimum values.